Celeste and Jesse forever [videorecording (DVD)] - Krieger, Lee Toland; Jones, Rashida; Samberg, Andy, 1978-; Wood, Elijah, 1981- (C&J Forever, LLC : Sony Pictures Home Entertainment [distributor], 2013)
Celeste and Jesse have been best friends since they can remember. High school sweethearts, they eventually got married--and now they're getting divorced. While their friends don't think the couple can stay friends after the divorce, Celeste and Jesse are determined to prove them wrong. But when Jesse begins dating again, Celeste finds it harder to move on than she thought it would be.